Research of hydrodynamics in the vacuum apparatus crystallization massecuite with a view to intensifying - Babko, Evhen; Litovchenko, Igor; Veresotskiy, Yuriy (My University, 2012)
Computer simulation of motion of the massecuite in vacuum-tube device with additional steam injection allowed us to obtain quantitative and qualitative data on the process of heat transfer. On the basis of studies of the process of heat transfer and hydrodynamics in a vacuum apparatus proposed upgrading unit batch.Комп'ютерне моделювання руху утфелю в трубці вакуум-апарата при додатковому вдуванні пари дозволило отримати якісні та кількісні дані про процес теплообміну.На підставі проведених досліджень процесу теплообміну і гідродинаміки у вакуум-апаратах запропонована модернізація апарату періодичної дії.
Keywords: massecuite; утфель; intensity; steam; intensity; пара; інтенсивність; пар; интенсивность; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра технологічного обладнання та комп’ютерних технологій проектування